C—C bond formation in the intramolecular Diels-Alder reaction of triene amides - Abdelilah Benallou; Habib El Alaoui El Abdallaoui; Hocine Garmes (Heliyon, 2018)
The mechanism nature of the intramolecular Diels–Alder reaction has been performed; and thus, the changes of C—C bond forming/breaking along IRC are characterized in this study. Conceptual DFT analyses of the most favorable adduct fused/exo shows that the flux electronic will take place from diene to dienophile moiety. Moreover, ELF topological analysis based on the electron density predicts that C—C bond is formed by the coupling of two pseudoradical centers generated at the most significant atoms of the molecules. However, C2 vs C3, also C1 and C4 interaction comes mainly from the global electron density transfer which takes place along the reaction. Two- stage one-step is the proposed mechanism of this reaction, the first stage aims for the formation of C2—C3 σ bond while the second stage aims for C1—C4 σ bond formation. Interestingly, the observed asynchronicity of this IMDA reaction due principally to the asymmetric reorganization of electron density at the most attractive centers.